Antibody responses to BNT162b2 mRNA vaccine: Infection‐naïve individuals with abdominal obesity warrant attention. Issue 3 (11th February 2022) - Malavazos, Alexis Elias; Basilico, Sara; Iacobellis, Gianluca; Milani, Valentina; Cardani, Rosanna; Boniardi, Federico; Dubini, Carola; Prandoni, Ilaria; Capitanio, Gloria; Renna, Laura Valentina; Boveri, Sara; Rigolini, Roberta; et al.
Abstract: Objective: The excess of visceral adipose tissue might hinder and delay immune response. How people with abdominal obesity (AO) will respond to mRNA vaccines against SARS‐CoV‐2 is yet to be established. SARS‐CoV‐2‐specific antibody responses were evaluated after the first and second dose of the BNT162b2 mRNA vaccine, comparing the response of individuals with AO with the response of those without, and discerning between individuals with or without prior infection. Methods: Immunoglobulin G (IgG)‐neutralizing antibodies against the Trimeric complex (IgG‐TrimericS) were measured at four time points: at baseline, at day 21 after vaccine dose 1, and at 1 and 3 months after dose 2. Nucleocapsid antibodies were assessed to detect prior SARS‐CoV‐2 infection. Waist circumference was measured to determine AO. Results: Between the first and third month after vaccine dose 2, the drop in IgG‐TrimericS levels was more remarkable in individuals with AO compared with those without AO (2.44‐fold [95% CI: 2.22‐2.63] vs. 1.82‐fold [95% CI: 1.69‐1.92], respectively, p < 0.001). Multivariable linear regression confirmed this result after inclusion of assessed confounders ( p < 0.001). Conclusions: The waning antibody levels in individuals with AO may further support recent recommendations to offer booster vaccines to adults with high‐risk medical conditions, including obesity, and particularly to those with a more prevalent AO phenotype.